TRANSFORMASI STRUKTURAL DAN KETIMPANGAN ANTAR KABUPATEN/KOTA DI JAWA BARAT - Kharisma, Bayu; Wardhana, Adhitya; Nur, Yudha Hadian (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
This research aims to analyze the structural transformation of the economy and inequality between regions that occur in the Region of West Java. Themethods used in this study are Location Quotient (LQ), Shift Share, Williamson Index and Entropy Theil analysis. Meanwhile, the types of data thatwill be used in this study are secondary data. Secondary data used in this study from 2011 to 2016. The results of the LQ analysis showed that thereare 7 (seven) regions that have an economic base in the industrial sector with Purwakarta as the largest contributory region. Meanwhile, 11 (eleven)regions in West Java Province have an economic base in the agricultural sector and the region that contributes the most is Cirebon. Furthermore, thereare 8 (eight) regions that have an economic base in the service sector with Bogor being the region that contributes the most. The level of incomeinequality in West Java Province decreased from 0.670 in 2010 to 0.646 in 2016. It shows the distribution of income that is increasingly evenlydistributed in the period 2010 - 2016 with the average - the largest level of inequality is Purwakarta. Meanwhile, the region with the smallest averagelevel of inequality is Bogor and the smallest level of inequality is Cianjur.